2009
DOI: 10.1021/jp907747w
|View full text |Cite
|
Sign up to set email alerts
|

Sulfur, Not Too Far Behind O, N, and C: SH···π Hydrogen Bond

Abstract: We report hydrogen-bonded complexes of H(2)S with indole and 3-methyl indole stabilized by the S-H...pi interaction. It is interesting to discover that although sulfur and its hydrides are known as poor hydrogen-bond donor/acceptors, sulfur is not too far behind oxygen, nitrogen, and carbon in regard to forming the pi-type hydrogen bonds. This report also extends the scope of our earlier studies from sigma-type hydrogen-bonded complexes of sulfur (O-H...S and N-H...S sigma-type hydrogen-bonded complexes) to pi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
101
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(108 citation statements)
references
References 89 publications
(178 reference statements)
4
101
0
2
Order By: Relevance
“…In addition to a lack of hydrogen atom resolution in the crystal structure, computational studies disagree whether the face of aromatic side chains preferentially interact with the lone pairs of the sulfur atom or through an SH-π interaction 47,49,50 . Our fluorination experiments are unable to distinguish between the two scenarios because both occur through an electrostatic interaction with the face of W6.48.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to a lack of hydrogen atom resolution in the crystal structure, computational studies disagree whether the face of aromatic side chains preferentially interact with the lone pairs of the sulfur atom or through an SH-π interaction 47,49,50 . Our fluorination experiments are unable to distinguish between the two scenarios because both occur through an electrostatic interaction with the face of W6.48.…”
Section: Discussionmentioning
confidence: 99%
“…Although its earliest conception considered only highly electronegative atoms like O, F, and N as donor and acceptors [1][2][3] , this picture has broadened considerably over recent years [4][5][6][7][8][9][10][11][12][13][14][15][16][17] . For example, despite some early resistance to the idea, the S atom is now recognized as a legitimate proton donor atom [18][19][20][21][22][23] . Also among those atoms which are now known to serve as proton donor is C, despite its nominally low electronegativity [24][25][26][27][28][29][30][31][32][33][34] .…”
Section: Introductionmentioning
confidence: 99%
“…2,7,8 Statistical analysis of the protein databank has shown that O-H···π, N-H···π, C-H···π and S-H···π interactions all occur frequently in proteins. 6,8,9 From theoretical studies it has been proposed that the electrostatic contribution to π-hydrogen bonding for different hydrogen bond donors decreases in the order of O-H ≈ S-H > N-H > C-H due to the differences in partial charges, 10,11 while the dispersion contribution decreases in the order of S-H > C-H > N-H > O-H due to trends in atomic polarizabilites (sulfur has a three times larger polarizability than oxygen and nitrogen). 1014 …”
Section: Introductionmentioning
confidence: 99%